2010
DOI: 10.1161/hypertensionaha.110.151860
|View full text |Cite
|
Sign up to set email alerts
|

Portal Osmopressor Mechanism Linked to Transient Receptor Potential Vanilloid 4 and Blood Pressure Control

Abstract: Abstract-Human subjects with impaired baroreflex function cannot buffer rises or falls in blood pressure (BP), thus allowing BP effects of endogenous or environmental stimuli that previously escaped detection to emerge dramatically. Studies in these patients led us to discover that water ingestion induced a robust increase in BP and vascular resistance. Here, using a mouse model of baroreflex impairment, we show that the increase in blood pressure after water ingestion is mediated through sympathetic nervous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
109
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(121 citation statements)
references
References 30 publications
9
109
1
Order By: Relevance
“…This concept is supported strongly by the outcome of studies in animals (McHugh et al. 2010). Gastric distension induced by a balloon increases muscle sympathetic nerve activity, the so‐called “gastrovascular reflex,” a response known to be attenuated in the healthy elderly (van Orshoven et al.…”
Section: Discussionmentioning
confidence: 99%
“…This concept is supported strongly by the outcome of studies in animals (McHugh et al. 2010). Gastric distension induced by a balloon increases muscle sympathetic nerve activity, the so‐called “gastrovascular reflex,” a response known to be attenuated in the healthy elderly (van Orshoven et al.…”
Section: Discussionmentioning
confidence: 99%
“…The information encoded by the electrical activity of these neurons is then relayed synaptically to diverse subsets of homeostatic effector neurons that induce appropriate osmoregulatory responses such as thirst, natriuresis, and antidiuretic hormone release (Denton et al, 1996;McKinley et al, 2006;Johnson, 2007;Bourque, 2008;Hollis et al, 2008). Interestingly, peripheral osmoreceptors located in the hepatoportal area are capable of detecting postingestion salt and water loads and modulating central osmoregulatory responses (Baertschi and Vallet, 1981;Choi-Kwon and Baertschi, 1991;McHugh et al, 2010;Lechner et al, 2011). It is presently unclear whether these peripheral receptors communicate independently with central effector neurons or if they modulate OVLT neurons via synaptic inputs (Bourque, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However the conclusion that Trpv1 encodes an osmore-ceptor channel was recently challenged because hypertonicityinduced expression of the immediate early gene Fos is maintained in the OVLT of mice lacking the gene (Taylor et al, 2008). Moreover, previous studies have indicated that another member of the TRPV gene family, Trpv4, is strongly expressed in the OVLT (Liedtke et al, 2000), and deletion of Trpv4 in mice attenuates Fos expression and osmoregulatory responses in vivo (Liedtke and Friedman, 2003;McHugh et al, 2010;Lechner et al, 2011). In this study we therefore examined the cellular basis for hypertonicity sensing in mouse OVLT neurons and determined whether this process requires expression of both Trpv1 and Trpv4.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in mice suggest that this osmopressor response may involve activation of transient receptor potential vanilloid 4 receptors, which may be located on putative peripheral osmoreceptors in the portal vein and liver. 33,34 However, the afferent nerve cell population serving as peripheral osmosensors and the exact transduction mechanisms are still not well understood. It should be emphasized that this osmopressor response is not induced by saline infusion and/or liquid containing the sodium chloride.…”
Section: Discussionmentioning
confidence: 99%